The conservation of mitochondrial genome sequence in Leucadendron (Proteaceae) - MADE PHARMAWATI; GUIJUN YAN; PATRICK M. FINNEGAN (Biodiversitas Journal of Biological Diversity, 2012)
Pharmawati M, Yan G, Finnegan PM. 2012. The conservation of mitochondrial genome sequence in Leucadendron (Proteaceae). Biodiversitas 13: 53-58. Mitochondrial DNA (mtDNA) is useful for developing molecular markers and for studying plant phylogeny.However, its usefulness depends on the degree of detectable sequence variation. In seven species of the genus Leucadendron, PCRRFLP failed to reveal any polymorphisms in seven separate regions of the mtDNA. Sixty-two primer pair - enzyme combinations were used to assay at least 248 restriction sites, resulting in the direct sampling of a minimum of 992 bp across 17,500 bp of mt DNA. The highly conserved nature of the mtDNA sequence in the genus Leucadendron was confirmed by the absence of sequence variation in the 1434 bp mtDNA nad1/B-C intron across these species. Mitochondrial DNA sequences are more highly conserved than the chloroplastDNA sequences in Leucadendron and the mtDNA sequences in many other plant genera. Phylogenetic analysis using this intronsequence was consistent with other phylogenetic analyses in regard to the position of Proteaceae.